2014
DOI: 10.1089/tmj.2013.0335
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Mobile Application for Personal Lifestyle Check-Up and Improvement

Abstract: Objective: This study aimed (1) to help individuals analyze their own health status by checking their lifestyle, (2) to develop a user-friendly mobile application that offered prescriptions for lifestyle improvement, and (3) to examine whether the developed application had positive effects on users. Materials and Methods: In order to develop a lifestyle analysis engine that would operate in an Android Ò (Google, Mountain View, CA)-based mobile application, survey data on health awareness behaviors of 25,124 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…These authors found that the use of the mobile app helped the assessments to be more efficient and accurate when compared to assessments completed via standard "paper-based" format. Others have documented the positive impact of apps on general physical wellness (e.g., Youm & Park, 2014), maternal health (e.g., Noordam, Kuepper, Stekelenburg, & Milen, 2011;Smith et al, 2014), treatment of eating disorders (e.g., Ambwanni, Cardi, & Treasure, 2014) and smoking cessation (e.g., Valdivieso-López et al, 2013), to name a few.…”
Section: Use Of Mobile Appsmentioning
confidence: 99%
“…These authors found that the use of the mobile app helped the assessments to be more efficient and accurate when compared to assessments completed via standard "paper-based" format. Others have documented the positive impact of apps on general physical wellness (e.g., Youm & Park, 2014), maternal health (e.g., Noordam, Kuepper, Stekelenburg, & Milen, 2011;Smith et al, 2014), treatment of eating disorders (e.g., Ambwanni, Cardi, & Treasure, 2014) and smoking cessation (e.g., Valdivieso-López et al, 2013), to name a few.…”
Section: Use Of Mobile Appsmentioning
confidence: 99%
“…Many studies have found that mobile apps can also increase productivity by improving personal lifestyles and information management. [24][25][26]37,38 Several studies used mobile devices in various aspects of health management, such as dietary improvement and motivation to exercise. [26][27][28] Regarding oral health issues, several applications were developed to provide knowledge about oral health care, to improve oral behaviour, to do oral health screening before referring to the dentist, and to assess the caries risk of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26]37,38 Several studies used mobile devices in various aspects of health management, such as dietary improvement and motivation to exercise. [26][27][28] Regarding oral health issues, several applications were developed to provide knowledge about oral health care, to improve oral behaviour, to do oral health screening before referring to the dentist, and to assess the caries risk of an individual. information by themselves so that they will know their risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations